2000
DOI: 10.1302/0301-620x.82b7.9791
|View full text |Cite
|
Sign up to set email alerts
|

Precision of the measurements of periprosthetic bone mineral density in hips with a custom-made femoral stem

Abstract: Our aim was to determine the precision of the measurements of bone mineral density (BMD) by dual-energy x-ray absorptiometry in the proximal femur before and after implantation of an uncemented implant, with particular regard to the significance of retro- and prospective studies. We examined 60 patients to determine the difference in preoperative BMD between osteoarthritic and healthy hips. The results showed a preoperative BMD of the affected hip which was lower by a mean of 4% and by a maximum of 9% compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 0 publications
1
26
0
2
Order By: Relevance
“…Caution must be exercised when interpreting and comparing results from different studies, since several influences must be considered such as: surgical approach (Perka et al 2005), definition of ROIs, leg position (Cohen and Rushton 1995a), pre-or postoperative baseline value (Kröger et al 1996), and cross-sectional or longitudinal studies (Martini et al 2000). However, a tendency towards a better retained proximal BMD has been found after implantation of thinner tapered stems without porous coating.…”
Section: Discussionmentioning
confidence: 99%
“…Caution must be exercised when interpreting and comparing results from different studies, since several influences must be considered such as: surgical approach (Perka et al 2005), definition of ROIs, leg position (Cohen and Rushton 1995a), pre-or postoperative baseline value (Kröger et al 1996), and cross-sectional or longitudinal studies (Martini et al 2000). However, a tendency towards a better retained proximal BMD has been found after implantation of thinner tapered stems without porous coating.…”
Section: Discussionmentioning
confidence: 99%
“…1 The cementless BicontactÂź stem is tapered, with a rough proximal hydroxyapatite coating and a smooth distal portion 20°internal rotation. The foot was secured in the Hologic foot positioning device in order to obtain reproducible rotation in all patients to limit measurement errors, as it has been demonstrated that rotation influences BMD measurement [9][10][11]. DEXA precision was assessed on all patients, and all underwent sequential DEXA examinations of the contralateral unoperated hip and the proximal femur-taken preoperatively and one week later.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of the device is a fit and fill pressfit into the proximal femur especially on the medial and lateral side. Martini et al were able to show in measurements of bone mineral density (BMD) that 10 days after operation there was a mean increase in the BMD of the replaced hip of 8% with a maximum of 24% [17]. Götze et al showed in cadaveric femurs a high primary stability in custom-made Adaptiva femoral stems with respect to subsidence, rotation, and interface motion [9].…”
Section: Discussionmentioning
confidence: 99%